High-throughput screening of printed carbon nanotube circuits using radio frequency heating. (November 2019) - Hicks, Victoria K.; Anas, Muhammad; Porter, Erin B.; Green, Micah J.
Abstract: In this paper, we demonstrate a high-throughput technique for screening carbon nanotube (CNT) circuits using radio frequency (RF) heating. It has become increasingly common to integrate carbon nanotubes into electronic devices because of their superior electrical and mechanical properties, and CNT-based circuits can be screen printed in mass quantities. Currently, the process for screening the quality of these circuits requires that the 2-point resistance of every circuit be measured individually; this metric is tedious, slow, and prone to false positives. We recently reported that CNTs experience heating when exposed to RF fields. Since the heating response is correlated with the conductivity of the printed structure, RF heating and thermal imaging allows us to quickly assess circuit quality. This new technique screens CNT circuits ten times faster than conventional methods, and it identifies faulty circuits more reliably. This process is not limited to CNT-based circuits, and it can be used to rapidly image any 2D structure made from an RF responsive material. Graphical abstract: Image 1